Behavioural, Biochemical, Proteomics Studies And Replacement Therapy Of Morphine And Mitragynine Withdrawal Rat Models - Hassan, Rahimah (2021)
The current study was designed to test the ability of mitragynine to attenuate behavioural signs of morphine-withdrawal in a rat model in comparison to methadone and buprenorphine. A six-day treatment with escalating dose of morphine (10-50 mg/kg, i.p.) induced profound withdrawal signs for 16 days.